Type tells tales - Heller, Steven 1950-; Anderson, Gail 1962- (Thames & Hudson, 2017)
"Stretching the boundaries of typographic expression, Type Tells Tales is a sensational showcase of type that is integral to the message it conveys, with the capacity to emote, engage, and guide the reader from one thought to the next. Navigating the far reaches of graphic design, Steven Heller and Gail Anderson reveal how type can render a particular voice or multiple conversations, how letters in various shapes and sizes can guide the eye through dense information, and how type can become both content and illustration, as letters take the form of people, animals, cars, or planes. The book's 332 illustrations - including 290 in color - feature historical examples by T.T. Marinetti, Bruno Munari, and Francis Picabia, among others, as well as by contemporary designers such as Richard Eckersley, John Hendrix, Maira Kalman, and Corita Kent. The book firmly locates the letter in the realm of artistry, finding exciting common ground among the pursuits of design, illustration, writing, and typography"--From jacket flap